Assesment of Optic Nerve Sheath Diameter in Healthy Adults in Turkey - Levent Albayrak; Emre Gökçen; İbrahim Çaltekin; Sevilay Vural; Nuray Kılıç; Hasan Burak Kaya; Mikail Kuşdoğan; Dilek Atik; Atakan Savrun (Sakarya Tıp Dergisi, 2021)
Introduction: In this study, we aimed to investigate how the normal values of optic nerve sheath diameter are distributed in normal healthy volunteers in Turkish population. Materials and Methods: This prospective study was planned between November 15, 2019 and April 15, 2020. The study included 160 healthy volunteers who were over 18 years of age and didn’t have acute and chronic systemic disorders. The optic nerve sheath diameters (ONSD) of the subjects were measured from both eyes ultrasonographically. Results: ONSD means (median, IQR) of right and left eyes of the subjects were measured as 4.87 (0.41) mm and 4.86 (0.32) mm, respectively. Right and left eye ONSD measurements were detected lower in female gender than men, and this difference was statistically significant. (p = 0.017 and p = 0.031, respectively). Conclusion: Determination of ONSD optimal reference values in healthy individuals would benefit in predicting increase in intracranial pressure in clinical practice.